2019
DOI: 10.4254/wjh.v11.i5.421
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus cure with direct-acting antivirals: Clinical, economic, societal and patient value for China

Abstract: About 10 million people in China are infected with hepatitis C virus (HCV), with the seroprevalence of anti-HCV in the general population estimated at 0.6%. Delaying effective treatment of chronic hepatitis C (CHC) is associated with liver disease progression, cirrhosis, hepatocellular carcinoma, and liver-related mortality. The extrahepatic manifestations of CHC further add to the disease burden of patients. Managing CHC-related advanced liver diseases and systemic manifestations are costly for both the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 119 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…16,17 Our study endorsed the results presented by Morad et al and Xie Q et al in Egyptian and Chinese populations respectively. 18,19 Similarly, Kesen O et al have the similar results in Turkish populations. 20 Contrary to our results, Thuluvath PJ et al showed only marginal improved in QoL after eradication of HCV.…”
Section: Discussionmentioning
confidence: 54%
“…16,17 Our study endorsed the results presented by Morad et al and Xie Q et al in Egyptian and Chinese populations respectively. 18,19 Similarly, Kesen O et al have the similar results in Turkish populations. 20 Contrary to our results, Thuluvath PJ et al showed only marginal improved in QoL after eradication of HCV.…”
Section: Discussionmentioning
confidence: 54%
“…[ 15 ] According to Xie et al ., a universal DAA adoption would reduce the cases of incident decompensated cirrhosis, hepatocellular carcinoma, liver transplants, and liver-related deaths by 61%, 45%, 50%, and 61%, respectively. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatitis B cirrhosis have benefited from years of oral antiviral therapy 13. On the other hand, for hepatitis C patients, direct acting antivirals as a new effective medication were not available during the study period 14…”
Section: Discussionmentioning
confidence: 99%